Bayesian modelling to estimate the test characteristics of coprology, coproantigen ELISA and a novel real‐time PCR for the diagnosis of taeniasis. Issue 5 (7th March 2013) - Praet, Nicolas; Verweij, Jaco J.; Mwape, Kabemba E.; Phiri, Isaac K.; Muma, John B.; Zulu, Gideon; van, Lisette; Rodriguez‐Hidalgo, Richar; Benitez‐Ortiz, Washington; Dorny, Pierre; Gabriël, Sarah
Abstract Objective To estimate and compare the performances of coprology, copro‐Ag ELISA and real‐time polymerase chain reaction assay (copro‐PCR) for detection of Taenia solium tapeworm carriers. Methods The three diagnostic tests were applied on 817 stool samples collected in two Zambian communities where taeniasis is endemic. A Bayesian approach was used to allow estimation of the test characteristics. Two (0.2%; 95% Confidence Interval (CI): 0–0.8), 67 (8.2%; 95% CI: 6.4–10.3) and 10 (1.2%; 95% CI: 0.5–2.2) samples were positive using coprology, copro‐Ag ELISA and copro‐PCR, respectively. Results Specificities of 99.9%, 92.0% and 99.0% were determined for coprology, copro‐Ag ELISA and copro‐PCR, respectively. Sensitivities of 52.5%, 84.5% and 82.7% were determined for coprology, copro‐Ag ELISA and copro‐PCR, respectively. Conclusions We urge for additional studies exploring possible cross‐reactions of the copro‐Ag ELISA and for the use of more sensitive tests, such as copro‐PCR, for the detection of tapeworm carriers, which is a key factor in controlling the parasite in endemic areas.